Coupling model and vibration simulations of railway vehicles and running gear bearings with multitype defects. (March 2021) - Lu, Zhenggang; Wang, Xiaochao; Yue, Keyu; Wei, Juyao; Yang, Zhe
Highlights: A nonlinear coupling dynamic model of a rail vehicle and axle box bearing is built. A novel and complete model of bearings with multitype defects is proposed. Bearing modeling strategy has a simple algorithm and high computational efficiency. Coupling model accurately simulates bearing vibration in train running conditions. Coupling model provides accurate simulated vibration signals for bearing diagnosis. Abstract: Axle box bearings are important parts of rail vehicle running gear. Currently, there is limited research on the coupling modeling of an axle box bearing and rail vehicle. In this paper, a complete method for bearing modeling with multitype defects is proposed. The bearing kinematics with three translation and one rotation degrees of freedom are analyzed and modeled, and defect modeling algorithms for the inner raceway, outer raceway and rollers are proposed. The theoretical rolling tracks of rollers passing through the defect points are analyzed and formulated. By coupling the bearing model to the motion joint of the shaft end and axle box, a closed-loop bearing-vehicle model is established. Model simulations show that the calculated results for normal bearings, different types of bearing defects and the bearing-vehicle coupling model are consistent with the theoretical values. The novel and complete coupling model proposed in this paper has the advantages of having a simple algorithm, high computational efficiency, and accurate simulation of the bearing vibration response under train running conditions, which can provide important guidance for research on the response of an axle box bearing in train running gear. By establishing a bearing-vehicle coupling model that simulates the bearing vibration response, especially when the bearings have faults, the performance of the defective bearing can be better understood and applied to develop diagnostic algorithms for the condition monitoring of axle box bearings in a rail vehicle.